Phylogenetic and phylogeographic analysis of Myrmeleotettix maculatus (Orthoptera: Acrididae: Gomphocerinae) species group in Anatolia - AKYILDIZ, GÜRKAN (MAGNOLIA PRESS, 2021)
Six Anatolian and one European populations of the Myrmeleotettix maculatus species group, which contains M. maculatus and M. ethicus species, have been studied by using molecular genetics methods with mitochondrial COI gene. Myrmeleotettix ethicus is an Anatolian endemic species with local distribution whereas M. maculatus is distributed in western Palearctic. The phylogenetic analysis (ML and BI analyses) of the M. maculatus species group in Anatolia reveals that it consistently recovered two well-supported main clades and four different lineages. Molecular time estimates suggest that the diversification of the M. maculatus species group took place between the Late Tortonian (around 8-9 My) and the Middle of Pliocene-Pleistocene (around 4.3 My?present) periods and the current distribution of the genetic diversity has been affected by the uplifting of the Central Anatolian plateau, the termination of the Messinian salinity crisis, and the Quaternary climatic changes.
Keywords: Myrmeleotettix maculatus; Orthoptera; Acrididae; COI; mitochondrial DNA; molecular phylogeny